(untitled) (Research, Society and Development, 2021)
Lipodystrophy is a dysfunction caused by the accumulation of fat cells in the tissue, which can be caused by several factors, such as heredity, bad posture, improper diet, among others. The 3 MHz therapeutic ultrasound is an equipment that shows to be very effective for the treatment of aesthetic dysfunctions, among them the irregular accumulation of fat. This is a literature review whose general objective was to evaluate the effects of therapeutic ultrasound associated with caffeine for the treatment of localized lipodystrophy. This study consisted of bibliographic research in electronic databases such as: Scientific Eletronic Library Online - Scielo, Bireme, and Google academic and LILACS (Scientific and Technical Literature from Latin America and the Caribbean). After selection and analysis of these materials it was identified the effectiveness of the ultrasound for the treatment of localized lipodystrophy, due to its thermal and mechanical effect thus agitating the molecules, and the caffeine with lipolytic effect. It is concluded that the existing literatures, there are several materials that prove the effectiveness of the US and caffeine, the association of both, can promote very satisfactory responses in the treatment of this aesthetic dysfunction.